Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(ĐK:a\ne1;a\ne0\)
\(A=\left[\frac{\left(a-1\right)^2}{3a+\left(a-1\right)^2}-\frac{1-2a^2+4a}{a^3-1}+\frac{1}{a-1}\right]:\frac{a^3+4a}{4a^2}=\left[\frac{a^2-2a+1}{a^2+a+1}-\frac{1-2a^2+4a}{a^3-1}+\frac{a^2+a+1}{a^3-1}\right].\frac{4a^2}{a^3+4a}\)\(=\left[\frac{a^3-3a^2+3a-1}{a^3-1}-\frac{1-2a^2+4a}{a^3-1}+\frac{a^2+a+1}{a^3-1}\right].\frac{4a^2}{a^3+4a}=\frac{a^3-1}{a^3-1}.\frac{4a}{a^2+4}=\frac{4a}{a^2+4}\)
b) Ta có: \(a^2+4\ge4a\)(*)
Thật vậy: (*)\(\Leftrightarrow\left(a-2\right)^2\ge0\)
Khi đó \(\frac{4a}{a^2+4}\le1\)
Vậy MaxA = 1 khi x = 2
![](https://rs.olm.vn/images/avt/0.png?1311)
\(A=4a\left(a+b\right)\left(a+b+c\right)\left(a+c\right)+b^2c^2\)
\(=4\left[a\left(a+b+c\right)\right]\left[\left(a+b\right)\left(a+c\right)\right]+b^2c^2\)
\(=4\left[a^2+ab+ac\right]\left[a^2+ac+ab+bc\right]+b^2c^2\)
Đặt \(a^2+ab+ac=t\)
Khi đó:
\(A=4t\left[t+bc\right]+b^2c^2\)
\(=4t^2+4tbc+b^2c^2\)
\(=\left(2t+bc\right)^2=\left(2a^2+2ab+2ac+bc\right)^2\ge0\forall a;b;c\)